SISTEM PAKAR MENDIAGNOSIS KERUSAKAN PADA KOMPUTER DENGAN MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Hendy Riven Refany .S; Alfannisa Annurrullah Fajrin (LPPM Universitas Putera Batam, 2024)
Along with the increasingly rapid development of technology in all aspects of life, it can be seen from the application of computerized system technology. Basically, computer damage problems are the most frequently encountered cases, such as slow computers when reading data, missing icons on the desktop, system application crashes or files that cannot be run, or error messages appearing that are not understood, these are the problems that arise It often has fatal consequences that interfere with the work or activities being carried out. Broadly speaking, computer damage problems can be divided into two categories, namely hardware damage and software damage. The purpose of this research is to diagnose damage to computers so that it can help computer users (users) to overcome problems or damage to computer hardware (hardware) and computer software (software), so as to save time and repair costs.